Exploration of Blast Resistant Genes and their Allelic Determinant in Sri Lankan Rice Varieties using their Domain Structures for Utilization in Breeding - Wijesinghe, T.; Suvanthini, T.; Kottearachchi, N.S. (Wayamba University of Sri Lanka, 2024)
Numerous rice blast resistance (R) genes have been identified, and a comprehensive understanding of their underlying mechanisms was deemed essential. Therefore, three major genes (Pb1, Pi21, and Pita) associated with rice blast (BL) were studied using genome sequences of 32 Sri Lankan rice varieties. The domain structure of each gene, Pb1, Pi21, and Pita of each variety was comprehensively analyzed in comparison to the three resistant varieties, Modan, Owarihatamochi, and Tetep. Results revealed that Alagusamba and Mudaligawee could be possessed relatively a stronger resistance compared to other varieties, due to the presence of complete pathogen recognition LRR domain which is necessary for triggering innate immunity. The resistant allele of the Pb1 gene is reported to contain two deletions with 21 bp and 48 bp giving rise to a low amount of proline amino acids, but such lengthy deletions could not be found in any of the Sri Lankan varieties. Few Sri Lankan varieties contained alanine at the 918th amino acid position which is considered as a feature of a resistant allele of the Pita gene. The results of the characterization of 32 Sri Lankan rice varieties regarding three blast-resistant genes would be useful for breeding rice for blast resistance
Keywords: Amino acid polymorphism; Blast; LRR domains; Magnaporthe oryzae; Molecular breeding